3.75X10^5 That seems to be the answer. You could type that in your calculator to see what you get.
Answer:
x = ± ![\sqrt{7}](https://tex.z-dn.net/?f=%5Csqrt%7B7%7D)
Step-by-step explanation:
To find the zeros equate the polynomial to zero, that is
x² - 7 = 0 ( add 7 to both sides )
x² = 7 ( take the square root of both sides )
x = ±
Thus the exact solutions are
x = -
, x = ![\sqrt{7}](https://tex.z-dn.net/?f=%5Csqrt%7B7%7D)
Answer:
(5,-2) or y=3(x-5)^2 -2
Step-by-step explanation:
The base case of
is trivially true, since
![\displaystyle P\left(\bigcup_{i=1}^1 E_i\right) = P(E_1) = \sum_{i=1}^1 P(E_i)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%5Cleft%28%5Cbigcup_%7Bi%3D1%7D%5E1%20E_i%5Cright%29%20%3D%20P%28E_1%29%20%3D%20%5Csum_%7Bi%3D1%7D%5E1%20P%28E_i%29)
but I think the case of
may be a bit more convincing in this role. We have by the inclusion/exclusion principle
![\displaystyle P\left(\bigcup_{i=1}^2 E_i\right) = P(E_1 \cup E_2) \\\\ P\left(\bigcup_{i=1}^2 E_i\right) = P(E_1) + P(E_2) - P(E_1 \cap E_2) \\\\ P\left(\bigcup_{i=1}^2 E_i\right) \le P(E_1) + P(E_2) \\\\ P\left(\bigcup_{i=1}^2 E_i\right) \le \sum_{i=1}^2 P(E_i)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%5Cleft%28%5Cbigcup_%7Bi%3D1%7D%5E2%20E_i%5Cright%29%20%3D%20P%28E_1%20%5Ccup%20E_2%29%20%5C%5C%5C%5C%20P%5Cleft%28%5Cbigcup_%7Bi%3D1%7D%5E2%20E_i%5Cright%29%20%3D%20P%28E_1%29%20%2B%20P%28E_2%29%20-%20P%28E_1%20%5Ccap%20E_2%29%20%5C%5C%5C%5C%20P%5Cleft%28%5Cbigcup_%7Bi%3D1%7D%5E2%20E_i%5Cright%29%20%5Cle%20P%28E_1%29%20%2B%20P%28E_2%29%20%5C%5C%5C%5C%20P%5Cleft%28%5Cbigcup_%7Bi%3D1%7D%5E2%20E_i%5Cright%29%20%5Cle%20%5Csum_%7Bi%3D1%7D%5E2%20P%28E_i%29)
with equality if
.
Now assume the case of
is true, that
![\displaystyle P\left(\bigcup_{i=1}^k E_i\right) \le \sum_{i=1}^k P(E_i)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%5Cleft%28%5Cbigcup_%7Bi%3D1%7D%5Ek%20E_i%5Cright%29%20%5Cle%20%5Csum_%7Bi%3D1%7D%5Ek%20P%28E_i%29)
We want to use this to prove the claim for
, that
![\displaystyle P\left(\bigcup_{i=1}^{k+1} E_i\right) \le \sum_{i=1}^{k+1} P(E_i)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%5Cleft%28%5Cbigcup_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20E_i%5Cright%29%20%5Cle%20%5Csum_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20P%28E_i%29)
The I/EP tells us
![\displaystyle P\left(\bigcup\limits_{i=1}^{k+1} E_i\right) = P\left(\left(\bigcup\limits_{i=1}^k E_i\right) \cup E_{k+1}\right) \\\\ P\left(\bigcup\limits_{i=1}^{k+1} E_i\right) = P\left(\bigcup\limits_{i=1}^k E_i\right) + P(E_{k+1}) - P\left(\left(\bigcup\limits_{i=1}^k E_i\right) \cap E_{k+1}\right)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20E_i%5Cright%29%20%3D%20P%5Cleft%28%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5Ek%20E_i%5Cright%29%20%5Ccup%20E_%7Bk%2B1%7D%5Cright%29%20%5C%5C%5C%5C%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20E_i%5Cright%29%20%3D%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5Ek%20E_i%5Cright%29%20%2B%20P%28E_%7Bk%2B1%7D%29%20-%20P%5Cleft%28%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5Ek%20E_i%5Cright%29%20%5Ccap%20E_%7Bk%2B1%7D%5Cright%29)
and by the same argument as in the
case, this leads to
![\displaystyle P\left(\bigcup\limits_{i=1}^{k+1} E_i\right) = P\left(\bigcup\limits_{i=1}^k E_i\right) + P(E_{k+1}) - P\left(\left(\bigcup\limits_{i=1}^k E_i\right) \cap E_{k+1}\right) \\\\ P\left(\bigcup\limits_{i=1}^{k+1} E_i\right) \le P\left(\bigcup\limits_{i=1}^k E_i\right) + P(E_{k+1})](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20E_i%5Cright%29%20%3D%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5Ek%20E_i%5Cright%29%20%2B%20P%28E_%7Bk%2B1%7D%29%20-%20P%5Cleft%28%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5Ek%20E_i%5Cright%29%20%5Ccap%20E_%7Bk%2B1%7D%5Cright%29%20%5C%5C%5C%5C%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20E_i%5Cright%29%20%5Cle%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5Ek%20E_i%5Cright%29%20%2B%20P%28E_%7Bk%2B1%7D%29)
By the induction hypothesis, we have an upper bound for the probability of the union of the
through
. The result follows.
![\displaystyle P\left(\bigcup\limits_{i=1}^{k+1} E_i\right) \le P\left(\bigcup\limits_{i=1}^k E_i\right) + P(E_{k+1}) \\\\ P\left(\bigcup\limits_{i=1}^{k+1} E_i\right) \le \sum_{i=1}^k P(E_i) + P(E_{k+1}) \\\\ P\left(\bigcup\limits_{i=1}^{k+1} E_i\right) \le \sum_{i=1}^{k+1} P(E_i)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20E_i%5Cright%29%20%5Cle%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5Ek%20E_i%5Cright%29%20%2B%20P%28E_%7Bk%2B1%7D%29%20%5C%5C%5C%5C%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20E_i%5Cright%29%20%5Cle%20%5Csum_%7Bi%3D1%7D%5Ek%20P%28E_i%29%20%2B%20P%28E_%7Bk%2B1%7D%29%20%5C%5C%5C%5C%20P%5Cleft%28%5Cbigcup%5Climits_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20E_i%5Cright%29%20%5Cle%20%5Csum_%7Bi%3D1%7D%5E%7Bk%2B1%7D%20P%28E_i%29)